2016
DOI: 10.1002/eat.22529
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions on body image and disordered eating outcomes among women in midlife

Abstract: Objective: Body dissatisfaction and disordered eating are widely recognised as issues that warrant attention among women in midlife, particularly the development and delivery of effective interventions. This paper systematically reviews existing research on interventions among midlife women on body image and disordered eating outcomes, in order to inform intervention delivery and provide strategic directions for future research. Method: Fourteen electronic databases were searched for articles published between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…With regard to exposure therapies, Koskina, Campbell, and Schmidt () conducted a systematic review and inter alia point to the potential of virtual‐reality settings for exposure techniques (see also Marco et al, ). Lewis‐Smith, Diedrichs, Rumsey, and Harcourt () as a result of their systematic review on body image interventions again in general call for more rigourous research on interventions in the field of body image in patients with AN.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to exposure therapies, Koskina, Campbell, and Schmidt () conducted a systematic review and inter alia point to the potential of virtual‐reality settings for exposure techniques (see also Marco et al, ). Lewis‐Smith, Diedrichs, Rumsey, and Harcourt () as a result of their systematic review on body image interventions again in general call for more rigourous research on interventions in the field of body image in patients with AN.…”
Section: Discussionmentioning
confidence: 99%
“…Changes of mean score of body image concern in period of study in intervention and control group age in students in the experimental group compared with the control group and a significant increase in self-esteem of students in the experimental group compared with the control group. Some studies have shown that education can reduce concerns about body image [4,[33][34][35][36], whereas others have shown that education has no effect on body image [22,37]. Controlled studies indicate that educational programs can significantly modify how an individual perceives his or her body [31].…”
Section: Discussionmentioning
confidence: 99%
“…An impaired body image can lead to problems such as loss of appetite, anorexia nervosa, abnormal weight change, sleep disorders, mental disorders, slow responses and unreasonable guilt, all of which represent public health problems [4,5]. Low self-esteem and lack of social support increase the vulnerability of an individual's self-image [6].…”
Section: Introductionmentioning
confidence: 99%